EFFECT OF TUBE DIAMETER AND SURFACE ROUGHNESS ON FLUID FLOW FRICTION FACTOR - Mirmanto, M.; Yudhyadi, IGNK; Sulistyowati, Emmy Dyah (Universitas Mataram, 2014)
Experiments have been performed to investigate the effect of channel roughness and diameter on fluid friction. Three different diameters and roughness of tubes were used to examine the friction factor. The first tube made of stainless steel with an inner diameter of 1.14 mm was investigated at Brunel University, whilst the others made of PVC with diameters of 17 mm and 15.5 mm rough were tested at Mataram University. The stainless steel was equipped with a 200 mm calming section and smooth one. The 15.5 mm diameter tube was coated internally with sand that had an average grain size of 0.5 mm so that the tube had a relative roughness of 0.032. The last tube with a diameter of 17 mm was smooth as explained in the H408 Fluid Friction Experimental Apparatus manual. The results indicate that the flow in the stainless steel tube still obeys the theory and in the 17 mm tube shows a deviation in friction factor with the theory. However, this was due to no calming section installed in the test rig. Flow in the rough tube (15.5 mm diameter) demonstrates that the Reynolds number does not affect the friction factor in turbulent regimes and the experimental friction factors were reasonably in a good agreement with the theory or Moody diagram. Hence, the effect of decreasing in diameter of channels on friction factor is insignificant.